The MOG antibody associated encephalitis preceded by COVID-19 infection; a case study and systematic review of the literature - Borończyk, Michał; Węgrzynek, Julia; Borończyk, Agnieszka; Siuda, Joanna (Frontiers in Neurology, 2023)
Background New neurological complications of COVID-19 infection have been reported in recent research. Among them, the spectrum of anti-MOG positive diseases, defined as anti-MOG antibody associated disease (MOGAD), is distinguished, which can manifest as optic neuritis, myelitis, or various forms of encephalitis (MOGAE). Materials and methods This study reports a new case of MOGAE following SARS-CoV-2 infection. A literature review of other MOGAE cases associated with COVID-19 infection was conducted and summarized. Results A 60-year-old male patient, who had previously been infected with COVID-19, was admitted to the Neurology Department with a rapidly progressive deterioration of his cognitive functions that lasted for about 3 months. On neurological examination, the Mini-Mental State Examination (MMSE) score was 17, which further deteriorated to 13. In addition, central paresis of the right VIIth nerve and pyramidal hemiparesis on the right side were noted. The MRI of the brain showed multiple hyperintense lesions. The CSF examination revealed an elevated total protein level with a normal cell count, and serum showed a positive finding of anti-MOG antibodies. Taking into account all the information, the diagnosis of MOGAE, following COVID-19 infection, was made. A total of 9 similar cases of MOGAE associated with SARS-CoV-2 infection were identified in the available literature. Among them 2 cases presented progressive cognitive dysfunction and another 5 altered mental status. The most frequently described MRI changes were hyperintense lesions located cortically and/or subcortically. Anti-MOG antibodies were positive in all patients. In 5 cases they were detected only in serum, in 2 cases in serum and CSF, and in 2 cases the origin was not reported. Conclusion The reported cases of MOGAE following COVID-19 infection suggest an increasing new clinical problem, and show an association between COVID-19 and MOGADs.